Each kindness - Woodson, Jacqueline; Lewis, Earl B. (New York : Nancy Paulsen Books, 2012)
When Ms. Albert teaches a lesson on kindness, Chloe realizes that she and her friends have been wrong in making fun of new student Maya's shabby clothes and refusing to play with her.
School Library Journal starred, September 2012.
Booklist starred, August 2012.
Pub Weekly, September 2012.
New York Times, October 2012.
Horn Book, January 2013.
Kirkus Review, May 2012.
Keywords: Kindness -- Juvenile fiction; Friendship -- Juvenile fiction; Schools -- Juvenile fiction; Kindness -- Fiction; Friendship -- Fiction; Schools -- Fiction; Friendship -- Fiction